Exploring Cognitive Domain Assessment Practices in Islamic Religious Education Learning at The Elementary School Level - Risa Melinda Septiani; Saepul Anwar; Ganjar Eka Subakti (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2026)
While cognitive assessment is crucial, elementary Islamic Religious Education (IRE) faces a specific pedagogical crisis: a severe disconnect between students' theoretical religious knowledge and actual moral behavior, exacerbated by curriculum overload and rigid evaluation metrics. This study analyzes the cognitive assessment ecosystem of Islamic Education learning to reveal how teachers understand, implement, strategize, and utilize assessment results in a public elementary school in Bandung. Employing a qualitative instrumental case study, five IRE teachers were purposively selected ensuring variation in teaching experience and grade levels to capture the full spectrum of cognitive developmental phases and guarantee data representativeness. Data were gathered via interviews, observations, and document analysis. Moving beyond the extensively researched finding that assessments stagnate at lower cognitive levels, this study reveals a novel epistemological dynamic: teachers pragmatically navigate the misalignment between heavy curriculum demands and students' cognitive readiness by implicitly merging cognitive evaluations with affective mechanisms and behavioral tracking. Resolving this crisis requires a transformative policy shift. Policymakers must systematically redesign the IRE assessment framework into an integrative-authentic model that formally bridges cognitive achievement with character actualization, empowering teachers as adaptive pedagogical designers.